Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 2 - Section 2.1 - The Additon Property of Equality - Exercise Set: 34

Answer

z = -6

Work Step by Step

5(3 + z) - (8z + 9) = -4z Apply distributive property: 5(3) + 5(z) - 8z - 9 = -4z 15 + 5z - 8z - 9 = -4z Combine like terms: -3z + 6 = -4z Add 4z to both sides: z + 6 = 0 Subtract 6 from both sides: z = -6 Check with substitution: 5(3 + (-6)) - (8(-6) + 9) = -4(-6) 5(-3) - (-48 + 9) = 24 -15 - (-39) = 24 24 = 24
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.